2013
DOI: 10.1371/journal.pone.0068950
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antiretroviral Therapy for the Prevention of Mother-To-Child Transmission of HIV in Malawi: Maternal and Infant Outcomes Two Years after Delivery

Abstract: BackgroundOptimized preventive strategies are needed to reach the objective of eliminating pediatric AIDS. This study aimed to define the determinants of residual HIV transmission in the context of maternal antiretroviral therapy (ART) administration to pregnant women, to assess infant safety of this strategy, and to evaluate its impact on maternal disease.Methodology/Principal FindingsA total of 311 HIV-infected pregnant women were enrolled in Malawi in an observational study and received a nevirapine-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 24 publications
2
49
1
Order By: Relevance
“…One study of 561 infants who received care between 2009 and 2012 in the Kilimanjaro Region of Tanzania reported 10% mother-to-child HIV transmission [25], despite the provision of prophylactic regimens that were expected to reduce vertical transmission to below 5% [12]. Another study of 311 mother–infant pairs in Malawi was able to reduce transmission to 3%, but 14% of infants died by 24 months of age [26]. …”
Section: Introductionmentioning
confidence: 99%
“…One study of 561 infants who received care between 2009 and 2012 in the Kilimanjaro Region of Tanzania reported 10% mother-to-child HIV transmission [25], despite the provision of prophylactic regimens that were expected to reduce vertical transmission to below 5% [12]. Another study of 311 mother–infant pairs in Malawi was able to reduce transmission to 3%, but 14% of infants died by 24 months of age [26]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the latter finding was not confirmed in a subsequent study (conducted in the same country on 300 women), which confirmed that BMI decreased more rapidly in breastfeeding women compared to those not breastfeeding, but showed that mortality did not differ significantly between formula feeders and breastfeeding mothers. 5 The very low mortality rate of women in our cohort (2.1% 2 years postpartum) 8 prevented us from assessing any possible difference in subsequent survival, but also suggested no major negative mortality impact.…”
mentioning
confidence: 84%
“…Patient population included women enrolled in the SMAC (Safe Milk for African Children) study, 8 conducted in Malawi between 2008 and 2011, within the DREAM program of the Community of S. Egidio, an Italian faith-based nongovernmental organization. In the study, aimed to assess the safety and pharmacokinetics of ART administration during breastfeeding, ART-naive women (with no grade 3 or 4 laboratory toxicity and no active tuberculosis) received either zidovudine plus lamivudine and nevirapine (n = 126) or stavudine plus lamivudine and nevirapine (n = 143) from week 25 of gestation until 6 months postpartum if their CD4 + count was > 350/mm 3 at baseline, or indefinitely if they met the criteria for treatment.…”
mentioning
confidence: 99%
“…Women enrolled in the Safe Milk for African Children (SMAC) [9] observational study, conducted in Malawi between 2008 and 2011 to evaluate safety of antiretroviral administration during pregnancy and breastfeeding, were studied.…”
mentioning
confidence: 99%